DEVELOPMENT OF PANCASILA STUDENTS’ PROFILE-THEMED PROBLEMS TO MEASURE THE FIFTH-GRADE STUDENTS' ABILITY IN SOLVING FRACTIONS PROBLEMS - Vivi Rachmatul Hidayati; Lalu Hamdian Affandi; Prayogi Dwina Angga; Linda Feni; Mega Puspita Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
In line with cognitive abilities, students’ skills in behavior (affective domain) are also required to be aligned with the Pancasila students’ profile. Students are expected to have characters, namely Faith, Pious to God Almighty, and noble character; Global Diversity; Working together; Creative; Critical Reasoning; and Independence. The purpose of this paper is to develop valid and reliable math questions with Pancasila students’ profile characteristics. The research used the instrument development method developed by Saifuddin Azwar, which includes setting goals, limiting the size domain, operationalization of behavioral aspects, item write-up, expert analysis, field trials, psychometric analysis, and final compilation. The development results indicate that 15 questions on fractions with different denominators are characterized by the Pancasila students’ profile. After validating the content and field trials validated by the expert in the form of construct validation, reliability, and discrimination tests, it was found that 15 questions were valid by 4 expert validators. 12 out of 15 questions were stated to be constructively valid, 12 questions were reliable, and 11 questions have good discriminatory power enough.